Wear performance of oleate-based esters with two-, three-, and four-branched molecular structure in pure form and mixture - Zulfattah, Z. M. (American Society of Mechanical Engineers, 2021)
This paper reports the optimization of base oils composition involving oleate-based bio-lubricant that results in minimal wear-scar diameter (WSD) and coefficient of friction (COF) using mixture technique (MT) with simplex-lattice design (SLD). The lubricants used were neopenthylglycol dioleate (NPGDO), trimethylolpropane trioleate (TMPTO), and pentaerythritol etraoleate (PETO), which all are products of transesterification process between oleic acid and different types of alcohols becoming oleate ester. Fourball tester (FBT) was used to evaluate the resulting COF under ASTM-D4172 B testing procedure, while WSD was measured under an optical wear-scar measuring device. A second-order polynomial mathematical model was built and able to statistically predict the resulting WSD and COF of lubricant mixtures. In pure form, PETO exhibited the lowest COF with 0.06555 followed by NPGDO (+5.25%) and TMPTO (+16.97%). Meanwhile, NPGDO recorded the smallest WSD with 0.451 mm, followed by PETO (+4.04%) and TMPTO (+8.89%). Under SLD optimization technique, pure PETO was shown to give out the lowest COF; however, the lowest WSD was recorded by a mixture of 80.661 wt% PETO with 11.603 wt% TMPTO, and 7.736 wt% NPGDO resulting in 0.444 mm WSD; 5.53% lower wear than pure NPGDO.